Interaction Forces and Morphology of a Protein-Resistant Poly(ethylene glycol) Layer - Heuberger, M.; Drobek, T.; Spencer, N.D. (Biophysical journal, 2005)
The molecular interactions on a protein-resistant surface coated with low-molecular-weight poly(ethylene glycol) (PEG) copolymer brushes are investigated using the extended surface forces apparatus. The observed interaction force is predominantly repulsive and nearly elastic. The chains are extended with respect to the Flory radius, which is in agreement with qualitative predictions of scaling theory. Comparison with theory allows the determination of relevant quantities such as brush length and adsorbed mass. Based on these results, we propose a molecular model for the adsorbed copolymer morphology. Surface-force isotherms measured at high resolution allow distinctive structural forces to be detected, suggesting the existence of a weak equilibrium network between poly(ethylene glycol) and water—a finding in accordance with the remarkable solution properties of PEG. The occurrence of a fine structure is interpreted as a water-induced restriction of the polymer's conformational space. This restriction is highly relevant for the phenomenon of PEG protein resistance. Protein adsorption requires conformational transitions, both in the protein as well as in the PEG layer, which are energetically and kinetically unfavorable.